Preparation and Performance Study of Photoconductive Detector Based on Bi2O2Se Film - Jun Liu; Zhonghui Han; Jianning Ding; Kang Guo; Xiaobin Yang; Peng Hu; Yang Jiao; Feng Teng (Photonics, 2023)
Bi2O2Se, as a novel two-dimensional semiconductor material, has been prepared and used in the field of photodetection. Herein, Bi2O2Se nanosheets were prepared using a hydrothermal method. Bi2O2Se films were also prepared using a drop-coating method. A photoconductive detector based on the Bi2O2Se film was constructed. The influence of nanosheet size was considered. Ultrasonic crashing treatments and different drying processes were used for the improvement of device performance. The obtained results demonstrate that the Bi2O2Se film based on treated nanosheets is denser and more continuous, leading to a higher photocurrent (1.4 nA). Drying in a vacuum can further increase the photocurrent of the device (3.0 nA). The photocurrent would increase with the increase in drying temperatures, while the dark current increases synchronously, leading to a decrease in the on/off ratio. The device based on Bi2O2Se film was dried in a vacuum at 180 °C and exhibited high responsivity (28 mA/W) and detectivity (~4 × 109 Jones) under 780 nm light illumination. Together, these results provide a data foundation and vision for the further development of photodetectors based on Bi2O2Se material.